A nanohybrid system based on covalently functionalized graphene quantum dots with dithienopyrrole derivative for the sensitive and selective fluorometric detection of Pb2+ ions. (24th July 2021) - Sebastian, Deepa; Soman, Sithara; R, Kala
Abstract: Recently graphene quantum dot (GQD) based nanohybrid materials have received much attention. Herein, a highly fluorescent biocompatible GQD and N‐functionalized dithienopyrrole (DTP‐PPD) modified nanohybrid system was fabricated (DTP‐PPD‐fn‐GQD) for the first time. Modification resulted in stable fluorescence with a quantum yield of approximately 22% and 36 nm redshift compared to unmodified GQD. The apparent bandgap tuning along with fluorescence property changes was investigated by cyclic voltammetry measurements and density functional theory studies. This water‐soluble system was then applied for the sensitive and selective detection of Pb 2+ ions. As a result of a specific interaction towards Pb 2+ ions, the fluorescence intensity was quenched. The detection limit is found to be 1.02 nM within the linear range of 3 to 30 nM. Finally, the feasibility of the developed probe was tested with real samples of water. Chemically modified GQDs are already widely exploited for Pb 2+ sensing, whereas GQD/thiophene‐based nanohybrid systems are less utilized. This newly developed nanohybrid of GQD (DTP‐PPD‐fn‐GQD) has excellent fluorescence properties and bandgap tunability. Moreover, effective fluorometric sensing of Pb 2+ ions in an aqueous medium is well investigated. This gives more insight into developing GQD‐based highly promising nanohybrid colorimetric as well as fluorescent sensors. Abstract : Synthesis and characterization of graphene quantum dot/N‐functionalized dithienopyrrole modified nanohybrids: fluorometric sensing of Pb 2+ ion and plausible mechanism was described.